Activities of institutions of higher spiritual education in Ukraine: administrative and legal guarantees - Чорнописька, Вікторія; Chornopyska, V. (Видавництво Львівської політехніки, 2022)
У статті проаналізовано адміністративно-правові гарантії діяльності закладів вищої духовної освіти в контексті сучасного освітнього законодавства України. З огляду на недостатній рівень науково-правового вивчення теми та зважаючи на інноваційні процеси в українському освітньому середовищі, наша розвідка певною мірою заповнює прогалини у дослідженні цієї проблематики. Незважаючи на задекларовані норми в освітньому законодавстві адміністративно-правові гарантії діяльності закладів вищої духовної освіти як релігійних організацій продовжуються формуватися. Нове освітнє законодавство заклало нові гарантії для закладів вищої духовної освіти та визначило нову траєкторію розвитку богословської освіти. Зокрема, законом зберігається автономність від Міністерства освіти і науки України, при цьому у результаті проходження акредитації заклади вищої духовної освіти можуть видавати диплом державного зразка. Законодавець дозволяє релігійним організаціям максимально корелювати освітню політику закладів вищої духовної освіти, визначати принципи діяльності студентського самоврядування. Щодо процедури ліцензування та акредитації, відкриття аспірантури та докторантури, спеціалізованої вченої ради зі спеціальності 041 «Богослов’я» законодавцем передбачаються істотні поступки та чітко визнаються всі документи закладів вищої духовної освіти які є еквівалентні державним документам. Втім, інституціалізація богослов’я в світській системі освіти вимагає пошуку нових форм її присутності в освітньо-науковому просторі України.

The article analyzes the administrative and legal guarantees of higher spiritual education in the context of modern educational legislation of Ukraine. Given the insufficient level of scientific and legal study of the topic and innovative processes in the Ukrainian educational environment, our article fills the gaps in the study of this issue to some extent. Despite the declared norms in the educational legislation, administrative and legal guarantees of the activity of higher spiritual education institutions as religious organizations continue to be formed. New educational legislation established new guarantees for institutions of higher spiritual education and set a new trajectory for the development of theological education. In particular, the law preserves the autonomy of the Ministry of Education and Science of Ukraine, and due to accreditation, institutions of higher spiritual education issue state diplomas. The legislator allows religious organizations to maximally correlate the educational policy of higher spiritual education institutions, and to determine the principles of student government. Regarding the procedure of licensing and accreditation, opening of postgraduate and doctoral studies, specialized academic council on specialty 041 “Theology”, the legislator provides significant concessions and clearly recognizes all documents of higher theological institutions that are equivalent to state documents. However, the institutionalization of theology in the secular education system requires the search for new forms in the educational and scientific space of Ukraine.
Діяльність закладів вищої духовної освіти в Україні: адміністративно-правові гарантії
Keywords: заклади вищої духовної освіти; адміністративно-правові гарантії; релігійні організації; Міністерство освіти і науки України; комітет Верховної ради України з питань освіти і науки; Закон України “Про вищу освіту”; institutions of higher spiritual education; administrative and legal guarantees; religious organizations; Ministry of Education and Science of Ukraine; Committee of the Verkhovna Rada of Ukraine on Education and Science; Law of Ukraine “On Higher Education”; 342.95; 348.328